Advanced sensing strategies for detecting zinc levels and zinc-related biomarkers in cancer pathogenesis - Daniela Vieira; Graziele Cruzado; Edward Harvey; Geraldine Merle (Sensing and Bio-Sensing Research)
Zinc and zinc-containing proteins are highlighted for their significant contributions to various physiological functions, with abnormal levels of these elements being associated with a wide range of diseases, including cancer, despite zinc itself not being considered a biomarker. Combining the detection of zinc and zinc-related biomarkers is an avenue to reliable and cost-effective monitoring. In this context, electrochemical sensing methods offer considerable advantages due to their rapid, simple, and cost-effective detection compared to standard methods. Recent advancements in electrochemical sensors have enhanced sensitivity for detecting low concentrations of zinc-related biomarkers present in early-stage cancer. Furthermore, incorporating carbon, gold, and bismuth nanostructures into sensor recognition elements enhances the capability for rapid, precise, and specific quantification of these biomarkers. This review discusses key zinc-related biomarkers, zinc levels and their roles in cancer development and progression, along with a comprehensive analysis of recent strategies to enhance the sensitivity and specificity of electrochemical sensors for zinc and zinc-related biomarkers.